The landmark book on Nicholas Rubakin - M. Dvorkina Ya.; М. Дворкина Я. (Scientific and Technical Libraries, 2021)
Review of the book: Stolyarov Yu. Rubakin revisited / Yury N. Stolyarov: Russian School Library Association Librarianship Department of the International Informatization Academy Russian State Library Research Center of Book Culture Studies of the Russian Academy of Sciences National Library of the Republic of Sakha (Yakutia). – Moscow : RUSLA, 2019. – 416 p., ill.The reviewer emphasizes the importance of the reviewed book, as Nicholas Rubakin’s work of researcher and educator, has not been studied comprehensively yet. The publication coincides with Rubakin’s 160-th anniversary. The reviewer characterizes the book structure and the contents of its five chapters: “The Life”, “The Foreign Native”, “The Focus of N. A. Rubakin’s Creative Interests”, “Bibliopsychological Portraits”, and “The Author of Integral Philosophy”.Yu. N. Stolyarov characterizes Nicholas Rubakin as a science communicator, expert of self-education and (kids) reading guidance and, most of all, as a founder of bibliopsychological theory. The reviewer examines the key works by Rubakin for each of the above-mentioned areas, e.g. “The secret of library work success”, “What the bibliological psychology is”, The Psychology of readers and books”, “Importance of the books”, “On the methodology of the book business”, “The book market in Soviet Russia and its psychology”. The reviewer makes a focus on Rubakin’s masterwork –“Among books” and on Stolyarov’s footnotes that expand the book text and reader knowledge, and points to the book design. Рец. на кн.: Столяров Ю. Н. Возвращённый Рубакин / Ю. Н. Столяров Ассоциация школьных библиотекарей русского мира Отделение «Библиотековедение» Международной академии информатизации Российская государственная библиотека Научный центр исследования книжной культуры РАН Национальная библиотека Республики Саха (Якутия). – Москва : РШБА, 2019. – 416 с., ил. В отзыве подчёркнута значимость рассматриваемой книги, поскольку творчество Н. А. Рубакина – замечательного учёного и просветителя – до сих пор не было достаточно полно раскрыто. Книга подготовлена к 160-летию со дня его рождения. Кратко представлены структура книги и содержание каждой из пяти её глав: «Жизненный путь», «Чужой среди своих», «Круг творческих интересов Н. А. Рубакина», «Библиопсихологические портреты», «Творец интегральной философии». Ю. Н. Столяров характеризует Н. А. Рубакина как популяризатора науки, специалиста по самообразованию и руководству чтением (в том числе детским), библиографа, библиотекаря и особо – как разработчика теории библиопсихологии. В каждой из перечисленных областей знания автор рассматривает основные произведения Н. А. Рубакина, например: «Где тайна успеха библиотечной работы», «Что такое библиологическая психология», «Психология читателя и книги», «Значение книги», «К методологии книжного дела», «Книжный рынок в советской России и его психология»; особо отмечает один из главных трудов Н. А. Рубакина – библиографический указатель «Среди книг». В рецензии обращено внимание на подстрочные примечания Ю. Н. Столярова, которые дополняют текст книги, расширяют знания читателя, а также на её оформление.